2012
DOI: 10.1186/1471-2369-13-30
|View full text |Cite
|
Sign up to set email alerts
|

Systematic comprehensive geriatric assessment in elderly patients on chronic dialysis: a cross-sectional comparative and feasibility study

Abstract: BackgroundElderly dialysis patients are prone to disabilities and functional decline. This aggravates their last period of life. It would be valuable to be able to preserve daily function and quality of life. Identification of domains requiring additional attention is not common practice in standard care. Therefore, we performed a systematic Comprehensive Geriatric Assessment (CGA) to assess physical and psychosocial function and tested its feasibility in daily practice. The CGA is used more frequently in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 43 publications
6
55
0
Order By: Relevance
“…A GA has been proposed as a supportive instrument for treatment decision making in ESRD as well (4,26). It provides the best available evidence on the patients' physiologic reserves and consequently, a better estimation of residual life expectancy (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A GA has been proposed as a supportive instrument for treatment decision making in ESRD as well (4,26). It provides the best available evidence on the patients' physiologic reserves and consequently, a better estimation of residual life expectancy (47).…”
Section: Discussionmentioning
confidence: 99%
“…Concrete information on impaired domains that could compromise dialysis treatment may facilitate shared decision making with the patient and relatives. In addition, it may reveal treatable conditions that would otherwise be overlooked (4,48), thereby forming a starting point for (preventive) interventions to optimize quality of life, such as physical and ADL impairments and social problems (45,49). Finally, the information derived from a GA may help to estimate adverse outcomes of surgical interventions (50) and other complex interventions (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also found that elderly dialysis patients frequently suffer from multiple geriatric impairments, not all of which are identified by the nephrology team. 24 This appears to be due in large part to the fact that these issues are not specifically looked for. In our study, we found that visual and hearing impairments, cognitive dysfunction and psychosocial issues were not reported most often.…”
Section: Discussionmentioning
confidence: 99%
“…8 Decreased functional capacity, sensory deficits, cognitive impairment and depression have frequently been found in hemodialysis (HD) patients [9][10][11] but only a few studies used comprehensive geriatric assessment (CGA) to evaluate HD patients. [11][12][13][14] CGA is a multidimensional procedure designed to evaluate an older person's physical health, functional ability, cognition and mental health, and socioenvironmental circumstances, as well as an extensive review of prescriptions. It was developed in order to improve coordination and integration of treatment and follow-up of elderly patients, together with the outcome.…”
Section: Introductionmentioning
confidence: 99%